Preparation method and application of nanoscale transition metal phosphide heterojunction catalyst

CN121272473BActive Publication Date: 2026-10-09SHANDONG HAIHUA GRP CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511854581.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-10
Publication Date
2026-10-09
Estimated Expiration
2045-12-10

AI Technical Summary

Technical Problem

[0006]本发明的目的是提供一种纳米级过渡金属磷化物异质结催化剂的制备方法和应用,可以解决传统高温焙烧和溶剂热法制备过渡金属磷化物催化剂过程中制备步骤复杂、反应时间较长、能耗较高、小尺寸和分散度难以同时实现、以及界面结构在整个催化剂中占比较低的问题

Benefits of technology

(1)本发明技术方案通过采用高温液相合成技术,实现了过渡金属磷化物催化剂从前驱体到成品的快速合成,与现有高温焙烧或溶剂热方法相比,显著简化了设备操作流程,反应时间由传统的小时级缩短至分钟级,大幅降低了能耗,制备效率显著提升,为规模化与工业化生产提供了可行路径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121272473B_ABST
    Figure CN121272473B_ABST
Patent Text Reader

Abstract

The application provides a preparation method and application of a nanoscale transition metal phosphide heterojunction catalyst, and belongs to the technical field of electrochemistry. First, cobalt acetylacetonate, nickel acetylacetonate, carbon black and tri-octylphosphine oxide are dispersed into a mixed solvent of oleylamine and 1-octadecene, then the mixed solution is subjected to joule heat treatment under an argon atmosphere, and finally, the nanoscale transition metal phosphide heterojunction catalyst is obtained through centrifugation, washing and drying. The preparation method has low cost and high efficiency, the prepared phosphide nanomaterial has small particle size, is highly dispersed on the carbon black, has a high proportion of interface structure, and has excellent performance in alkaline electrolytic water hydrogen gas extraction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical technology, specifically relating to a method for preparing and applying a nanoscale transition metal phosphide heterojunction catalyst. Background Technology

[0002] To address these challenges, researchers are actively exploring clean energy solutions, including solar, tidal, wind, and hydrogen energy. Hydrogen energy, in particular, with its high energy density, small molecular weight, and the fact that it uses only water as a combustion product, is considered a crucial component of the future energy system. Among numerous hydrogen production technologies, alkaline water electrolysis has become a key pathway for hydrogen production due to its ease of operation and readily available raw materials. However, the low efficiency and high energy consumption of traditional alkaline water electrolysis methods limit its widespread application, creating an urgent need for high-performance, low-cost, and highly stable catalysts.

[0003] Currently, platinum (Pt) is considered one of the most effective catalysts for the hydrogen evolution reaction (HER) in water electrolysis. However, the scarcity and high price of platinum severely hinder its large-scale application in hydrogen production. Therefore, scientists are dedicated to exploring lower-cost and more abundant non-precious metal catalysts as alternatives. Transition metal phosphides (TMPs), due to their structural similarities to naturally occurring hydrogenases and their stable catalytic activity, have shown great potential as HER catalysts, especially their bifunctional capabilities in catalyzing both hydrogen evolution and oxygen evolution reactions, indicating broad application prospects in the future energy field. However, traditional synthesis methods for these transition metal phosphides, including high-temperature calcination and solvothermal methods, often involve complex steps, long reaction times, and high energy consumption. Long reaction times often result in large phosphide sizes, and even when small-sized catalysts are obtained, catalyst aggregation is often unavoidable. These factors lead to fewer catalytically active sites in the prepared phosphide catalysts, resulting in poor catalytic activity. In addition, the proportion of interfacial structures in phosphide heterojunction materials prepared by traditional methods is still relatively low, making it difficult to fully utilize the regulatory effect of metastable local interfaces on the electronic structure of the central metal. This, to some extent, limits the further improvement of their catalytic performance.

[0004] Chinese invention patent document CN116804280A discloses a nickel phosphide-cobalt phosphide hollow microsphere composite, its preparation method, and its application. This patent first prepares a nickel-cobalt carbonate hydroxide precursor via a hydrothermal method, and then prepares the nickel phosphide-cobalt phosphide hollow microsphere composite through a prolonged high-temperature gas-solid phase phosphating reaction. The material preparation method disclosed in this patent is cumbersome, time-consuming, and energy-intensive, making it unsuitable for large-scale applications.

[0005] Chinese invention patent document CN111668501A discloses a fuel cell anode catalyst, its preparation method, and its application. This patent first mixes a transition metal source and trioctylphosphine oxide in a reaction vessel and reacts under vacuum at 90-150°C for 5-60 minutes. Then, the reaction system is filled with inert gas and heated to a reaction temperature of 180-400°C. A predetermined amount of phosphorus source is added, and the reaction temperature is maintained for 0.1-6 hours. Finally, after cooling, washing, and vacuum drying, the reaction product is obtained and then loaded onto a carbon support to obtain a carbon-supported composite phosphide catalyst. This method involves a complex preparation process and a long heating time, which is not conducive to the preparation of small-sized nanoparticles. Furthermore, the carbon support and phosphide are composited through mechanical mixing, making it difficult to achieve highly uniform dispersion, and the internal binding capacity of the material is weak, resulting in limited improvement in catalytic activity and stability. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing and applying nanoscale transition metal phosphide heterojunction catalysts, which can solve the problems of complex preparation steps, long reaction time, high energy consumption, difficulty in simultaneously achieving small size and dispersion, and low proportion of interfacial structure in the entire catalyst in the traditional high-temperature calcination and solvothermal methods for preparing transition metal phosphide catalysts.

[0007] To achieve this objective, the technical solution of the present invention is as follows: A method for preparing a nanoscale transition metal phosphide heterojunction catalyst includes the following steps: (1) Disperse cobalt acetylacetonate, nickel acetylacetonate, carbon black, and trioctylphosphine oxide in a mixed solvent of oleylamine and 1-octadecene, and stir for 0.5-1 h to obtain a precursor solution; (2) The precursor solution was subjected to Joule heat treatment under an argon atmosphere. The crude product was centrifuged, washed and dried to obtain Co2P / Ni2P / C, i.e., nanoscale transition metal phosphide heterojunction catalyst. In step (1), the usage of cobalt acetylacetonate, nickel acetylacetonate, carbon black, trioctylphosphine oxide, oleylamine, and 1-octadecene is in the following ratio: 1 mg: 1~3 mg: 3~5 mg: 0.02~0.08 mL: 0.2~0.5 mL: 0.2~0.5 mL; In step (2), the Joule heat treatment conditions are: under an argon atmosphere, the heating temperature is 350~600℃, the heating rate is 1000~3000℃ / s, and the holding time is 1~10min.

[0008] Further, in step (2), the centrifugation conditions are: centrifugation speed 10000-15000 rpm, time 3-5 min; washing conditions are: using a mixed solvent of n-hexane and anhydrous ethanol with a volume ratio of 1:1, washing 2-4 times; drying conditions are: temperature 60-80℃, time 1-2 h.

[0009] Another object of the present invention is to provide an application of the nanoscale transition metal phosphide heterojunction catalyst prepared by the above method, using it as an electrochemical catalyst in the hydrogen evolution reaction (HER) under alkaline electrolyte.

[0010] Compared with the prior art, the present invention has the following beneficial effects: (1) The technical solution of the present invention realizes the rapid synthesis of transition metal phosphide catalysts from precursors to finished products by adopting high-temperature liquid phase synthesis technology. Compared with existing high-temperature calcination or solvothermal methods, it significantly simplifies the equipment operation process, shortens the reaction time from the traditional hours to minutes, greatly reduces energy consumption, and significantly improves preparation efficiency, providing a feasible path for large-scale and industrial production.

[0011] (2) By employing Joule heating technology to achieve ultra-rapid heating (1000~3000℃ / s), the reaction system was heated to the target temperature in an extremely short time, enabling effective control of the nucleation and growth kinetics of nanoparticles. This significantly suppressed excessive growth and aggregation of particles, ensuring that the final catalyst had an ultra-small nanoscale size (less than 10 nm). This precise control of size is key to improving intrinsic catalytic activity, as verified by Comparative Example 3: the catalyst prepared by the traditional slow heating method at 10 mA·cm -2 The overpotential at current density is as high as 125mV, which is significantly higher than that of the catalyst prepared by the ultra-fast heating technology of this invention (54~64mV).

[0012] (3) This invention achieves efficient reduction and phosphating of metal precursors (cobalt acetylacetonate and nickel acetylacetonate) under high-temperature reaction conditions by using an optimized mixed solvent system of oleylamine and 1-octadecene (ODE) and synergistically using trioctylphosphine oxide as both a ligand and a phosphorus source. This solvent system not only effectively dissolves and disperses all precursors (including the carbon black support), but its properties (such as high boiling point, reducing power, and coordination ability) also ensure that the phosphating reaction proceeds fully and rapidly in a homogeneous environment. More importantly, this system enables in-situ generation and uniform loading of phosphide nanoparticles on the carbon black support, avoiding the problems of uneven dispersion and weak interfacial bonding caused by subsequent mechanical mixing, thereby significantly improving the activity and stability of the catalyst.

[0013] (4) The nanoscale transition metal phosphide heterojunction catalyst prepared by the technical solution of the present invention has the advantages of small particle size, high dispersion and uniform loading on the support. Compared with the single phosphide or phosphide heterojunction obtained by traditional methods, the catalyst has a higher proportion of interface structure in the material, which can maximize the synergistic effect of the two components, and significantly optimize the electronic structure of the central metal atom under the regulation of the metastable local interface, thereby effectively improving the number and utilization efficiency of catalytic reaction active sites.

[0014] (5) The nanoscale transition metal phosphide heterojunction catalyst prepared in this invention exhibits excellent alkaline water electrolysis hydrogen production performance, 10 mA•cm -2 The overpotential at current density is only 54~64 mV, compared to commercial Pt / C (52mV@10mA•cm). -2 The performance is similar to that of hydrogen produced in other materials, and it exhibits sustained stability during the 48-hour electrocatalytic process with no significant performance degradation. This performance advantage makes it a promising candidate for applications in clean energy conversion and industrial hydrogen production. Attached Figure Description

[0015] Figure 1 X-ray powder diffraction pattern of the nanoscale transition metal phosphide heterojunction catalyst prepared in Example 1; Figure 2 Transmission electron microscopy (TEM) images of the nanoscale transition metal phosphide heterojunction catalyst prepared in Example 1, where Figures a and b are TEM images of the sample in Example 1 at different regions and different magnifications, respectively. Figure 3 Example 1: Linear sweep voltammetry (LSV) curves of the catalyst-modified electrode prepared from the nanoscale transition metal phosphide heterojunction catalyst. Figure 4 The electrode modified with the nanoscale transition metal phosphide heterojunction catalyst prepared in Example 1 operates at 10 mA•cm. -2 Timing potential diagram under current density. Detailed Implementation

[0016] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention, but the scope of protection of the present invention is not limited thereto.

[0017] Unless otherwise specified, the equipment, instruments, and raw materials used in the embodiments of the present invention are all commercially available products; unless otherwise specified, all technical and scientific terms used in the present invention have the same meaning as commonly understood by those skilled in the art. Example 1

[0018] (1) Disperse 4 mg cobalt acetylacetonate, 8 mg nickel acetylacetonate, and 16 mg carbon black in a mixed solution of 0.2 mL trioctylphosphine oxide, 1.5 mL oleylamine, and 1.5 mL 1-octadecene, and stir for 0.8 h to obtain a mixed solution precursor; (2) 3 mL of the mixed solution precursor was transferred to a quartz boat (10 mL) fixed in the groove of a graphite heating plate and subjected to Joule heat treatment under an argon atmosphere at a temperature of 500 °C and a heating rate of 2500 °C / s for 5 min. The crude product was cooled and washed three times by centrifugation with a 1:1 volume ratio of hexane and anhydrous ethanol at a speed of 12500 rpm for 4 min. The product was then dried at 70 °C for 1.5 h to obtain Co2P / Ni2P / C, i.e., a nanoscale transition metal phosphide heterojunction catalyst. Example 2

[0019] (1) Disperse 4 mg of cobalt acetylacetonate, 4 mg of nickel acetylacetonate, and 12 mg of carbon black in a mixed solution of 0.08 mL of trioctylphosphine oxide, 0.8 mL of oleylamine, and 0.8 mL of 1-octadecene, and stir for 0.5 h to obtain a mixed solution precursor; (2) 3 mL of the mixed solution precursor was transferred to a quartz boat (10 mL) fixed in the groove of a graphite heating plate and subjected to Joule heat treatment under an argon atmosphere at a temperature of 350 °C and a heating rate of 1000 °C / s for 10 min. The crude product was cooled and washed twice by centrifugation with a 1:1 mixture of n-hexane and anhydrous ethanol at a speed of 10000 rpm for 3 min. The product was then dried at 60 °C for 2 h to obtain Co2P / Ni2P / C, i.e., a nanoscale transition metal phosphide heterojunction catalyst. Example 3

[0020] (1) Disperse 3 mg cobalt acetylacetonate, 9 mg nickel acetylacetonate, and 15 mg carbon black in a mixed solution of 0.24 mL trioctylphosphine oxide, 1.5 mL oleylamine, and 1.5 mL 1-octadecene, and stir for 1 h to obtain a mixed solution precursor. (2) 3 mL of the mixed solution precursor was transferred to a quartz boat (10 mL) fixed in the groove of a graphite heating plate and subjected to Joule heat treatment under an argon atmosphere. The Joule heat treatment temperature was 600 °C, the heating rate was 3000 °C / s, and the holding time was 1 min. After cooling, the crude product was washed four times by centrifugation with a mixed solvent of n-hexane and anhydrous ethanol in a volume ratio of 1:1 at a speed of 15000 rpm for 5 min. The product was then dried at 80 °C for 1 h to obtain Co2P / Ni2P / C, i.e., a nanoscale transition metal phosphide heterojunction catalyst. Comparative Example 1

[0021] The difference between Comparative Example 1 and Example 1 is that in step (1), the amount of cobalt acetylacetone used is 12 mg and the amount of nickel acetylacetone used is 0 mg, while the rest of the methods are the same as in Example 1. Comparative Example 2

[0022] The difference between Comparative Example 2 and Example 1 is that in step (1), the amount of cobalt acetylacetone used is 0 mg and the amount of nickel acetylacetone used is 12 mg, while the rest of the methods are the same as in Example 1. Comparative Example 3

[0023] (1) Same as step (1) in Example 1; (2) Transfer the mixed solution obtained in step (1) to a round-bottom flask and reflux at 180°C for 3 hours in an argon atmosphere. After cooling the crude product, wash it three times by centrifugation with a mixed solvent of n-hexane and anhydrous ethanol in a volume ratio of 1:1. The centrifugation speed is 10000-15000 rpm and the centrifugation time is 3-5 min.

[0024] Application Example 1

[0025] The examples, comparative samples, and commercial Pt / C catalysts were used in HER applications under alkaline conditions, including the following application steps: 5 mg of catalyst was dispersed in a mixed solvent (composed of 0.45 mL ethanol, 0.5 mL deionized water, and 50 μL of 0.5% Nafion solution), and sonicated for 1 h to obtain a uniformly dispersed catalyst solution. The catalyst solution was then drop-coated onto a glassy carbon electrode to achieve a loading of 0.5 mg / cm³. 2 After natural air drying, a catalyst-modified glassy carbon electrode was obtained. Electrochemical tests were performed on a rotating ring disk test system and a CHI760E electrochemical workstation. The catalyst-modified glassy carbon electrode was used as the working electrode, the carbon rod as the counter electrode, and Ag / AgCl as the reference electrode. Linear sweep voltammetry (LSV) tests of the HER reaction were performed in 1M KOH aqueous solution. The test results are shown in Table 1.

[0026] The HER performance test results of Examples 1-6, Comparative Examples 1-3, and commercial Pt / C are shown in the table below:

[0027] Table 1 shows the HER performance test results of Examples 1-3, Comparative Examples 1-3, and commercial Pt / C. As can be seen from the figure, the nanoscale Co2P / Ni2P / C catalysts prepared in the examples exhibited good performance at 10 mA•cm⁻¹. -2 The overpotential at current density is only 54~64mV, compared to commercial Pt / C (52mV@10mA•cm). -2The performance of the single-phase Co2P (142 mV @ 10 mA • cm⁻¹) prepared in Comparative Example 1 is similar to that of the control group, and it exhibits significantly enhanced hydrogen evolution reaction (HER) performance. The fundamental reason for this performance difference lies in the fact that, compared to the control group, the single-phase Co2P (142 mV @ 10 mA • cm⁻¹) prepared in Comparative Example 1... -2 Single-phase Ni₂P (130mV@10mA•cm) prepared in Comparative Example 2 -2 Comparative Example 3 (125mV@10mA•cm) prepared by conventional methods -2 Compared to other methods, the nanoscale Co2P / Ni2P / C heterojunction catalyst with a high interface ratio prepared by the high-temperature liquid-phase impact method can fully leverage the synergistic effect of the two phosphide components, maximize the creation of metastable local interface structures, and significantly adjust the electronic structure of the central metal atom, thereby greatly improving the catalytic performance of transition metal phosphides.

[0028] Figure 1 The X-ray powder diffraction pattern of Example 1 is shown. As can be seen from the figure, the XRD characteristic pattern of Example 1 is consistent with the Ni2P standard card (PDF#03-0953) and the Co2P standard card (PDF#54-0413), indicating that Example 1 is composed of two phases, Ni2P and Co2P.

[0029] Figure 2 The transmission electron microscope (TEM) image of Example 1 is shown. Figure 2 As can be seen from Figure a, the phosphide prepared in Example 1 possesses both small particle size and high dispersibility, exhibits highly uniform loading on the support, and has a high proportion of interfacial structure. This is further demonstrated by high-magnification transmission electron microscopy. Figure 2 As shown in b, two closely connected crystal particles have lattice spacings of 0.19 nm and 0.17 nm, corresponding to the (209) crystal plane of Ni2P and the (002) crystal plane of Co2P, respectively. These two crystals are closely connected and form a Co2P-Ni2P heterojunction interface. In addition, the size of both crystal particles is less than 10 nm. This nanoscale Co2P / Ni2P / C heterojunction catalyst with a high interface ratio can give full play to the synergistic effect of the two phosphide components, maximize the creation of a metastable local interface structure, and significantly adjust the electronic structure of the central metal atom, thereby improving the catalytic performance of transition metal phosphides.

[0030] Figure 3 Linear sweep voltammetry (LSV) curves of the electrodes modified with the commercial Pt / C catalysts of Example 1 are shown. As can be seen from the figures, at the same potential, Example 1 and the commercial Pt / C exhibit similar current densities, indicating that the catalytic activity of Example 1 is close to that of the commercial Pt / C, demonstrating its great potential as a replacement for Pt group catalysts in achieving hydrogen production through water electrolysis.

[0031] Figure 4The nanoscale transition metal phosphide heterojunction prepared in Example 1 is demonstrated under a constant current density of 10 mA·cm⁻¹. -2 The hydrogen evolution reaction (HER) stability test results were used to further evaluate the long-term stability of the synthesized material. As shown in the figure, Example 1 exhibited sustained stability during the 48-hour electrocatalytic process without significant performance degradation, indicating that the nanoscale Co2P / Ni2P / C heterojunction catalyst with a high interface ratio prepared by the high-temperature liquid-phase impact method has great potential to replace Pt group catalysts in achieving hydrogen production through water electrolysis.

Claims

1. A method for preparing a nanoscale transition metal phosphide heterojunction catalyst, characterized in that, Includes the following steps: (1) Disperse cobalt acetylacetonate, nickel acetylacetonate, carbon black, and trioctylphosphine oxide in a mixed solvent of oleylamine and 1-octadecene, and stir for 0.5-1 h to obtain a precursor solution; (2) The precursor solution was subjected to Joule heat treatment under an argon atmosphere. The crude product was centrifuged, washed and dried to obtain Co2P / Ni2P / C, i.e., nanoscale transition metal phosphide heterojunction catalyst. In the nanoscale transition metal phosphide heterojunction catalyst, Co2P crystal particles and Ni2P crystal particles are closely connected to form a Co2P-Ni2P hetero interface, and the size of the crystal particles is less than 10 nm. In step (1), the usage of cobalt acetylacetonate, nickel acetylacetonate, carbon black, trioctylphosphine oxide, oleylamine, and 1-octadecene is in the following ratio: 1 mg: 1~3 mg: 3~5 mg: 0.02~0.08 mL: 0.2~0.5 mL: 0.2~0.5 mL; In step (2), the Joule heat treatment conditions are: under an argon atmosphere, the heating temperature is 350~600℃, the heating rate is 1000~3000℃ / s, and the holding time is 1~10min.

2. The method for preparing the nanoscale transition metal phosphide heterojunction catalyst according to claim 1, characterized in that, In step (2), the centrifugation conditions are: centrifugation speed 10000-15000 rpm, time 3-5 min; washing conditions are: using a mixed solvent of n-hexane and anhydrous ethanol with a volume ratio of 1:1, washing 2-4 times; drying conditions are: temperature 60-80℃, time 1-2 h.

3. The application of a nanoscale transition metal phosphide heterojunction catalyst prepared by the method described in claim 1 or 2, characterized in that, The catalyst was applied to the alkaline water electrolysis hydrogen evolution reaction.

Citation Information

Patent Citations

  • Fuel cell anode catalyst and preparation method and application thereof

    CN111668501A

  • Nickel phosphide-cobalt phosphide hollow microsphere compound as well as preparation method and application thereof

    CN116804280A

  • Carbon-supported discrete platinum group metal-non-noble metal phosphide full-electrolysis water electric catalyst as well as preparation method and application thereof

    CN118616065A